(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
Five brinjal (Solanum melongena L.) genotypes were selected for characterization using Simple Sequence Repeats (SSR) markers. All the genotypes showed considerable variation in respect of morphological, anatomical and biochemical aspects. For study of relatedness, plant genomic DNA was extracted by CTAB based method using 11 randomly selected primers produced from Calgene Inc. USA. The primers developed 22 bands through PCR amplification out of which 15 from 3 primers and were polymorphic. Genetic similarities of SSR profiles were estimated based on Jaccards coefficient value. The dendrogram generated two clusters and they were clearly distinct and separated from each other. Cluster-I consisted of genotypes TURBO and BL009; and cluster-II comprised of genotypes EG058, EG075 and ISD006. Genotype TURBO and BL009 were identified as the diverse genotype and showed a maximum of 17% dissimilarity from EG058, EG075 and ISD006. The similarity value ranged from 0.83 to 1.00 which indicated the presence of narrow range of genetic diversity at molecular level but have still a possibility of crossing among the genotypes of two clusters. The banding pattern of different genotypes could be utilized as reference for further comparisons. DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17041